Les femmes et l’approche du Buen Vivir en Bolivie : entre l’absence et l’émergence - Cécile Collinge; Juan-Luis Klein (Revue Interventions Économiques)
At the beginning of the XXIe century, the Bolivian government gave a prominent place to the indigenous lifestyle, inspired by the Buen Vivir approach. This approach was raised as an alternative to the dominant western paradigm of development. It was constitutionalized and promoted as a way of life in Bolivia. What is the place of women in this new context? According to B. de Sousa Santos, Bolivian indigenous women are ’absent’ from the ’emergent’ approach which is the Buen Vivir. From a feminist geography perspective, we met Bolivian women, professionals as well as indigenous, and we asked them about the repercussions of the implementation of Buen Vivir on their lives.